2014
DOI: 10.1016/j.euroneuro.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

ASP5736, a novel 5-HT5A receptor antagonist, ameliorates positive symptoms and cognitive impairment in animal models of schizophrenia

Abstract: We recently identified ASP5736, (N-(diaminomethylene)-1-(3,5-difluoropyridin-4-yl)-4-fluoroisoquinoline-7-carboxamide (2E)-but-2-enedioate), a novel antagonist of 5-HT5A receptor, and here describe the in vitro and in vivo characterization of this compound. ASP5736 exhibited a high affinity for the human 5-HT5A receptor (Ki = 3.6 ± 0.66 nM) and antagonized 5-carboxamidotryptamine (5-CT)-induced Ca(2+) influx in human cells stably expressing the 5-HT5A receptor with approximately 200-fold selectivity over other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…These patterns of tissue localization suggest the involvement of this receptor in a proportion of psychiatric disorders. We recently observed that a novel 5-HT 5A antagonist ligand attenuated cognitive dysfunction in several animal models of schizophrenia (7). In the present study, we evaluated the effects of novel 5-HT 5A antagonists on cognitive dysfunction associated with dementia such as the cholinergic deficit and aged rat models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patterns of tissue localization suggest the involvement of this receptor in a proportion of psychiatric disorders. We recently observed that a novel 5-HT 5A antagonist ligand attenuated cognitive dysfunction in several animal models of schizophrenia (7). In the present study, we evaluated the effects of novel 5-HT 5A antagonists on cognitive dysfunction associated with dementia such as the cholinergic deficit and aged rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has implicated changes in PFC monoamine signaling in age-related working passive avoidance learning (26,27). In a recent immunohistochemistry study, we observed that 5-HT 5A receptors are co-expressed on DA neurons (tyrosine hydroxylase-positive) in the ventral tegmental area (VTA) (7). We therefore hypothesize that 5-HT 5A receptor antagonists block inhibitory 5-HT 5A receptors on DA neurons in the VTA, which enables projection to the mPFC and thereby improves cognitive impairment by activating DA neurons in the mPFC.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…A preclinical study demonstrated that blocking and stimulation of 5-HTR5A might impair and facilitate short- and long-term memory, respectively [ 150 ]. On the other hand, the 5-HTR5A antagonist ASP5736 improved positive and cognitive symptoms in a schizophrenia mouse model as well as in aged rats and mice with scopolamine-induced working memory deficit [ 151 , 152 ]. These data suggest that ASP5736 may be used in the treatment of cognitive defects in schizophrenic patients.…”
Section: Serotonin Receptors (5-htr)mentioning
confidence: 99%
“…Of course further investigation is necessary, meanly with selective 5-HT 5A compounds (Gonzalez et al, 2013 ). Interestingly, Yamazaki et al ( 2014 , 2015 ) reported that a 5-HT 5A receptor antagonist ameliorates positive symptoms and cognitive impairment in animal models of schizophrenia and in aged rats and induced-amnesia. An analogous case is observed regarding 5-HT 1A partial agonists (see above).…”
Section: Memory Tasks and Molecular Changesmentioning
confidence: 99%